(3CMcGe GdbQGfGJs - (3eMeO Hf YHO Gddg Hf YeQ Hf GdHGRjGQ GdHZOGOj,J (B245 (3g` s
(3ChdgG (B:s
(3cJGH ai Led ef OdGdGJ GdCTNGU GdYGdjI Ydi GdCMOGK GdcGFfI ai YGde Gdchf hGdaSGO ef LgI eMdgG YfO WhGdY GdHhGOi GdbQGfjI s
(3BNQgG (B:s
(3heJi hGab HYV GdCTNGU GdYGdjI ai CReGf GdJMhjdjI TgGOGJ EOdGA GdaQOGQGJ Ch ZjQgG , cGf Pdc Cbhi ddEeGdI hCUOb HeTjFI Gddg hJhajbI Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B1s
(3ai KeGfjI ebGdGJs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B447 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B14s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1324s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs